Rainwater-harvesting measures at BARC, Trombay, Mumbai: a case study. (21st February 2007) - Srivastava, P.K.; Agarwal, Alok; Mehra, K.B.; Tewari, P.K.; Ramanujam, S.; Kulkarni, P.B.
The rapid dwindling of fresh water resources has focused worldwide attention on water conservation measures and integrated water management. Rain, the important component of the hydrological cycle, has therefore received enormous attention, and Rainwater Harvesting (RWH) has emerged as one of the most important and economical tools of water conservation. Bhabha Atomic Research Centre, with its expansive area, terrain characteristics and scientific know-how, has been able to create nearly 400 million litres of reservoir capacity by implementing RWH measures. It has further identified an additional 150 million litre capacity buildup. Additional proposals are being implemented for greater non-potable use of harvested water, hitherto confined to gardening. Cost analysis of fresh proposals reveals the return period to be less than five years.